Introducción al concepto de empresa periodística en Internet - Cea Esteruelas, Mª Nereida (Estudios sobre el Mensaje Periodístico, 2010)
The major media groups have created companies specific to the Internet market that take the form of business units within the organisation, thus adhering to other activities such as publishing or broadcasting. The article proposes the definition of the model adopted by these media companies, and establishes its differential elements as a starting point. Independence in their organisation, as one of the companies within the group, is challenged by their dependence on other media. This is due to the convergent nature of the Internet that, within the media group, operates, not so much as another media but as a new digital parent company where the different information markets converge.